Score - Ryan, Kennedy (Hollywood Renaissance, 2026)
"You never forget your first love. Isn't that what they say? Verity Hill knows this truth intimately. She didn't simply miss Wright "Monk" Bellamy when they parted ways in college. She's haunted by his touch. Every kiss, any lover since-it's a shadow of what they had. Time heals all wounds. Isn't that what they say? Monk doesn't believe that for a second. He wasn't simply betrayed when he and Verity split. He was devastated, with parts of him left behind in the ruins of all that was destroyed. More than a decade after their disastrous breakup, Verity and Monk must work together on the set of an epic Harlem Renaissance biopic. With Monk, now a world-class musician, creating the score, and Verity, an award-winning screenwriter, penning the script, there's Oscar buzz before shooting even begins. This once-in-a-lifetime project could catapult them both to new heights, but can they put the past behind them for the sake of the film...for the sake of something more?"-- Provided by publisher.